Experimental and numerical investigation on the compressive properties of interlocking blocks. (1st February 2021) - Shi, Tingwei; Zhang, Xihong; Hao, Hong; Chen, Chong
Highlights: A laboratory, analytical and numerical study of interlocking brick is presented. The effect of the number of blocks/surface roughness/material strength is studied. A formula is modified to predict compressive strength of interlocking bricks. A semi-empirical prediction method is derived to predict the axial stiffness. Abstract: Masonry construction with interlocking bricks could effectively reduce construction time, minimize labour cost and improve construction quality. Existing interlocking bricks are mostly designed to provide easy alignment only, therefore the effect of interlocking mechanism on the mechanical performance of the interlocking block is not well investigated. This paper presents a laboratory and numerical study on the mechanical properties of a new type of interlocking brick featured with large shear keys for better mechanical performance. The theoretical compressive strength of a unit brick prism is derived using fracture mechanics theory, which is validated with laboratory compression test. Then, further tests on prisms with multiple interlocking bricks show the number of bricks strongly influences the performance of prism compressive strength. Detailed 3D numerical models of interlocking brick prisms are generated using ABAQUS. The numerical modelling results are compared with experimental test results. The damage and failure modes of the interlocking blocks are numerically and experimentally studied. Localized stress concentration at block interlocking surfaces is investigated. Parametric study is then carried out to quantify the influences of different design parameters including the number of blocks, brick surface roughness amplitude due to brick manufacturing tolerance and surface unevenness, and material strength. A modified formula based on the analytical solution is derived by fitting the numerical simulation and experimental results to predict the compressive capacity of interlocking brick prisms. A semi-empirical prediction method is also derived to predict the axial stiffness of the interlocking brick prism for use in design analysis of masonry structures made of mortar-less interlocking bricks.